Profiling IgG and IgA antibody responses during vaccination and infection in a high-risk gonorrhoea population - Stejskal, L; Thistlethwaite, A; Ramirez-Bencomo, F; Rashmi, S; Harrison, O; Feavers, IM; Maiden, MCJ; Jerse, A; Barnes, G; Chirro, O; Chemweno, J; Nduati, E; et al. (Nature Research, 2024)
Development of a vaccine against gonorrhoea is a global priority, driven by the rise in antibiotic resistance. Although Neisseria gonorrhoeae (Ng) infection does not induce substantial protective immunity, highly exposed individuals may develop immunity against re-infection with the same strain. Retrospective epidemiological studies have shown that vaccines containing Neisseria meningitidis (Nm) outer membrane vesicles (OMVs) provide a degree of cross-protection against Ng infection. We conducted a clinical trial (NCT04297436) of 4CMenB (Bexsero, GSK), a licensed Nm vaccine containing OMVs and recombinant antigens, comprising a single arm, open label study of two doses with 50 adults in coastal Kenya who have high exposure to Ng. Data from a Ng antigen microarray established that serum IgG and IgA reactivities against the gonococcal homologs of the recombinant antigens in the vaccine peaked at 10 but had declined by 24 weeks. For most reactive OMV-derived antigens, the reverse was the case. A cohort of similar individuals with laboratory-confirmed gonococcal infection were compared before, during, and after infection: their reactivities were weaker and differed from the vaccinated cohort. We conclude that the cross-protection of the 4CMenB vaccine against gonorrhoea could be explained by cross-reaction against a diverse selection of antigens derived from the OMV component.